Our Power that Grants More Power: The Role of the Communicator in Effective Electoral Campaigns - Saavedra Vargas, Guadalupe (2023)
This article aims to explain the relevance of the communicator in an electoral campaign team and how new technologies and trends in 2023 challenge them to use mechanisms of political communication suitable for their campaign strategy. Therefore, the political context of the last electoral campaigns in the country, the most relevant steps to build the electoral campaign, and the role of the communicator during this electoral process are emphasized. In conclusion, “our power that grants more power” invites communicators who are part of the decision-making for a company, institution or even for the country, to reflection and introspection.